Association between Clinical Manifestations of Systemic Sclerosis and Esophageal Dysmotility Assessed by High-Resolution Manometry. Issue 1 (January 2017) - de Carlan, Marine; Lescoat, Alain; Brochard, Charlène; Coiffier, Guillaume; Cazalets, Claire; Ropert, Alain; Jégo, Patrick
Purpose: To characterize esophageal involvement according to high-resolution manometry (HRM) findings using the 3 rd version of the Chicago Classification, in a French population of patients fulfilling the ACR/EULAR 2013 classification criteria for systemic sclerosis (SSc). Methods: Thirty-six patients were consecutively included in this cross-sectional non-interventional study and had HRM performed in Rennes University hospital. Demographic and clinical characteristics, SSc history and interstitial lung disease (ILD) on CT-scan were assessed, and compared with esophageal motility. Results: Sixty-one percent of SSc patients had ineffective peristalsis (55.6% failed peristalsis and 5.6% weak peristalsis), 33.3% had hypotensive esophagogastric junction pressure, 75% did not have a physiologic contraction following multiple rapid swallow (MRS), and 44.4% had an abnormal peristaltic reserve. One patient had type 1 achalasia and another one had Jackhammer esophagus. Failed peristalsis was associated with pyrosis (odds ratio [OR] 7.28, 95% confidence interval [CI] 1.51-35.21, p = 0.009), a higher modified Rodnan skin score (MRSS) (without failed peristalsis: 4.68 ± 2.95 vs. with failed peristalsis: 10.68 ± 9.23; p<0.05), the presence of telangiectasia (OR 7, 95% CI 1.59-30.8, p = 0.007), and low diffusing capacity of the lung for carbon monoxide (DLCO) (p = 0.013). Food in the esophagus and esophageal dilation on CT-scan were associated with failed contractions on HRM (respectively, OR 6.85, 95% CI 1.12-40.82, p = 0.05, and OR 14.67, CI 2.4-88.5, p = 0.002). Conclusions: This study confirms that failed peristalsis is frequent in SSc and associated with other organ involvement. We found a concordance between HRM results and CT-scan findings regarding esophageal involvement.